Investigation of the effect of the addition H2O2 on the general corrosion of brass in hydrochloric acid - Kasapović, Dejana; Bikić, Farzet (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2022)
In this paper, the influence of hydrochloric acid and the addition of oxidizing agents on the rate of general corrosion of brass was investigated. For comparison, the corrosion rate of copper and zinc in hydrochloric acid and in hydrochloric acid with oxidizing agent was also tested. The Taffel extrapolation method was used to examine the general corrosion of brass, copper and zinc. The Taffel extrapolation method involves scanning potential of the working electrode of ±250 mV in relation to its open-circuit otential (EOCP), at a speed of 0.5 mVs-1. Investigation of corrosion was conducted in a corrosion cell according to the ASTM G5 (ASTM G5-94) standard, on a potentiostat/galvanostat instrument, Princeton Applied Research, model 263A-2, with PowerCORR® software, which is part of the Power Suite softwere package. The tests were performed at room temperature, 20±1°C. The results show that the corrosion rate of brass is higher in hydrochloric acid with oxidizing agent than the corrosion rate of brass in hydrochloric acid. Examining the effect of hydrochloric acid and the addition of oxidizing agent on the rate of general corrosion of brass, it was found that the corrosion of brass has caused the zinc contained in it. Corrosion of zinc is highest in 0.1 M HCl + 0.1 M H2O2 compared to corrosion of brass and copper in 0.1 M HCl + 0.1 M H2O2, where corrosion of copper is lowest in 0.1 M HCl + 0.1 M H2O2.